Inovasi Pembelajaran Diagram Batang Berbantuan Media Pakudiba Melalui Pendekatan PMRI Kelas IV SDN Demangan - Husna, Dika Aida; Susendra, M. Ari; Zuliana, Eka (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
This research aims to enhance students' understanding of bar chart material by utilizing innovative learning media, specifically Pakudiba (Bar Chart Cube Board), implemented through the Indonesian Realistic Mathematics Education (PMRI) approach in the fourth grade at SDN Demangan. The study employs a qualitative descriptive method, with data collection techniques including observation, interviews, and documentation. The findings indicate that the Pakudiba media effectively improves students' concentration, active participation, and comprehension of bar chart concepts. The PMRI approach also proves effective in helping students connect mathematical concepts to real-life situations, making learning more meaningful. Challenges encountered include differences in students' abilities, the need for additional time, and the costs associated with providing the tools. Overall, the Pakudiba media has been shown to be effective in enhancing the quality of mathematics education, particularly in presenting data using bar charts.